The Educational Inequalities in the Disadvantaged Social Strata of Romani Population. Issue 3 (11th September 2020) - Özbaş, Mehmet
Abstract : The objective of this study is to determine the variables that create inequality for children from disadvantaged social strata in their process of compulsory education. The study was carried out in Erzincan, which is a significant city located in the eastern Anatolia region of Turkey, in 2017. Nearly, 117 parents from disadvantaged social strata participated in the study. Disadvantaged children face the most serious problems in education. Those families were poor and disadvantaged Romanies, so their children did not attend the school. The study reveals that the inhabitants of a disadvantaged social stratum of this study mostly come from the ethnic origin of Romanies. This study was designed in a descriptive research model and carried out with face‐to‐face interview method. The semi‐structured interview form of "Educational Inequalities in Disadvantaged Social Strata" was used in this study. The semi‐structured interview form has been developed for this study. The study also reveals that 76 percent of disadvantaged families are not able to receive any proper economic support from the state they needed for their children. The disadvantaged families claim that authorities have never told them the true meaning, significance, and functions of compulsory education. In addition, the study reveals that the biggest obstacles are having poorly educated parents and financial insecurity for disadvantaged families in terms of their social, economic, and individual growth. The study reveals that the lack of continuous cash transfers to the students of disadvantaged strata creates social injustice and inequality in compulsory education. It is highly recommended that continued economic support should be given for the students from disadvantaged families to meet their basic psychological and human needs. Abstract : 本研究检验了城市穷人的概况和生计策略。通过使用阿克拉市三个易贫困地区的原始数据, 本研究追溯了216名贫穷城市青年的流动史, 并试图得知其如何应对城市生计。研究结果表明, 研究对象并未获得过任何正式的社会保护援助, 也未从家庭处获得非正式援助, 并且几乎没有社交团体/联系。研究对象所采纳的应对策略包括: 小额交易(36.2%)、街头"kayayee"(25.5%)、街头贩卖(12.8%)以及推卡车(10.6%)。一些研究对象还参与了非法及非道德活动, 例如偷窃(以男性为例)和卖淫(以女性为例)。研究建议, 鉴于大多数研究对象曾经辍学, 并且超过了政府提供的新免费高中教育所规定的年龄, 则应鼓励开展技能与职业培训以帮助其摆脱贫困。 Abstract : El objetivo de este estudio es determinar las variables que generan desigualdad para los niños de estratos sociales desfavorecidos en su proceso de educación obligatoria. El estudio se llevó a cabo en Erzincan, que es una ciudad importante ubicada en la región oriental de Anatolia de Turquía, en 2017. 117 padres de estratos sociales desfavorecidos participaron en el estudio. Los niños desfavorecidos se enfrentan a los problemas más graves de educación. El estudio revela que los habitantes de un estrato social desfavorecido de este estudio provienen en su mayoría del origen étnico de los romaníes. Este estudio fue diseñado en un modelo de investigación descriptivo y realizado con el método de entrevista presencial. En el estudio se utilizó la forma de entrevista semiestructurada de "Desigualdades educativas en estratos sociales desfavorecidos". El estudio también revela que el 76% de las familias desfavorecidas no pueden recibir ningún apoyo económico adecuado del estado que necesitaban para sus hijos. El estudio revela que la falta de transferencias monetarias continuas a los estudiantes para los estratos desfavorecidos genera injusticia social y desigualdad en la educación obligatoria. Se recomienda encarecidamente que se brinde apoyo económico continuo a los estudiantes de familias desfavorecidas para satisfacer sus necesidades psicológicas y humanas básicas.